2018
DOI: 10.2478/ssa-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biomass ash, lime and gypsum fertilization on macro- and microelement contents in the soil and grains of spring wheat

Abstract: The addition of lime and gypsum to wood ash and straw ash were used in the studies. The subject of the study was estimation of the fertilization effect of biomass, ash, gypsum and lime on the content of macro- and microelements in soil and grain of spring wheat. The experiment was carried out in 2016 in the West Pomeranian Voivodeship in Poland. The study compared three factors: wood ash of deciduous and coniferous trees and cereal straw ash (I. factor), two types of ash additions: lime or gypsum (mixture comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 15 publications
4
15
3
Order By: Relevance
“…It is also noteworthy that there was a relatively high content of Mn-3840 mg•kg −1 , Zn-236 mg•kg −1 , Cr-230 mg•kg −1 and Cu-66.4 mg•kg −1 ( Table 5). The content of Ca in the ash was high compared to the findings of References [16,23,24]; it oscillates around the highest value of the content found by Ribbing [43] and is well below the value reported by other authors [2,6,17,25,26]. In general, the content of Ca in ash biomass varies greatly depending on its origin, ranging from 3.6 to 35.3% [12].…”
Section: Analysis Of Ash Propertiescontrasting
confidence: 50%
See 3 more Smart Citations
“…It is also noteworthy that there was a relatively high content of Mn-3840 mg•kg −1 , Zn-236 mg•kg −1 , Cr-230 mg•kg −1 and Cu-66.4 mg•kg −1 ( Table 5). The content of Ca in the ash was high compared to the findings of References [16,23,24]; it oscillates around the highest value of the content found by Ribbing [43] and is well below the value reported by other authors [2,6,17,25,26]. In general, the content of Ca in ash biomass varies greatly depending on its origin, ranging from 3.6 to 35.3% [12].…”
Section: Analysis Of Ash Propertiescontrasting
confidence: 50%
“…The content of Fe should be regarded as relatively low when compared to the results in references [2,17,43] but it is high in the context of the other data [12,23,25,26]. A medium content of Mg was found when compared to the results in references [2,16,17,43] but it was high in the context of the other data [23,25,26].…”
Section: Analysis Of Ash Propertiesmentioning
confidence: 57%
See 2 more Smart Citations
“…The authors also noted that the P content in grain and straw increased when SSA was applied at 65.4 kg P/ha, but no SP at the same P dose was applied to compare, so this result is inconclusive. Other field studies on recycling P products, such as ashes made of wood and cereal straw, also showed results similar to ours, with no effect on P content in wheat grain [66] or the same effect on P content in barley grain and straw as the SP applied at the same P dose performed [67].…”
Section: In P Content P Accumulationsupporting
confidence: 87%